Students’ Perceptions Of Their Readiness, Self-Learning Motivation And Attitude Toward English Online Learning During Covid-19 Pandemic At High Schools In North Makale - Angelia Repal; Syarifuddin Dolla; Sudirman Maca (Jounal of Primary Education, 2022)
The research aimed at describing how students studied during the Covid-19 pandemic, the process of shifting from a face-to-face learning to online learning. In order to achieve these aims, the researcher designed three main objectives: to find out students’ readiness in English online learning, students’ motivation in English online learning and student’ attitude towards English online learning. The researcher applied the quantitative method. The samples were chosen randomly from 65 students within 7 different high schools in North Makale. The data analyzed was in quantitative research involved summarizing data dependably and accurately.   The result showed that the students are not fully ready for English online learning during the Covid-19 Pandemic. The lack of infrastructure such as internet access is the major obstacle to the implementation of distance learning in schools, especially in North Makale. Furthermore, the samples are not confident computer and internet users, and they also demonstrate low self-efficacy issue in doing online learning. The students’ motivation toward English online learning was inconsistent even thought it is categorized in a moderate degree of motivation. Some students prefer face-to-face learning process than online learning and think that the previous one will give them a better learning result. It becomes a challenge for teachers to prepare the teaching materials, teaching strategies and the methods well before the English online learning.